The Image of the General Elections Commission (KPU) in the 2024 Presidential Election - N. Novalia; Rindana Intan Emeilia; Arina Muntazah; Rosiana Andhikasari (Golden Ratio of Data in Summary, 2024)
Throughout the organization of presidential elections in Indonesia, the General Elections Commission (KPU) has often been in the public spotlight. In this context, the image of the KPU, which consists of trust, reality, cooperation, and awareness, serves as the indicators used by the public to evaluate the institution. This research employs a qualitative methodology and is based on a literature review of previous studies and surveys conducted by several independent organizations. Surveys by Kompas Research and Development (Litbang Kompas) and Databoks support this assessment. The results show that public trust in the KPU has declined due to political dispute issues, with a score of 277. However, according to the Litbang Kompas survey on the reality indicator, the public perceives the KPU's image positively, with a score of 62%. On the cooperation indicator, public political participation in the presidential election continues to increase. Regarding the awareness aspect, the lack of public political knowledge is a critical point in Indonesian politics. Therefore, as the institution responsible for organizing elections, the KPU needs to continuously improve its performance and image.